Legal, Moral, and Spiritual Dialectics in the Islamic Restorative Justice System - Ali Sodiqin (AHKAM : Jurnal Ilmu Syariah, 2021)
Islamic law is special and unique since it is from revelation. In restorative justice systems, Islam integrates legal, moral, and spiritual aspects in its enforcement. The integration of these three aspects is clear in the philosophy of law, legal construction, and the determination of legal actions and sanctions. The purpose of this study is to examine the integration of these three aspects in forming a restorative justice model through the classification of authority (ḥuqūq) in Islamic law. According to the law, the classification of God and human rights and the mixture of these two determines different models of restorative justice enforcement. In general, the law rules in God’s authority (ḥuqūq Allāh) and produces the enforcement of offender centered models of restorative justice through repentance (tawbat) and redemption (kaffārāt). Furthermore, it also rules under human authority (ḥuqūq al-’abd) and in a mixture of the two rights, producing a victim-centered model of restorative justice through compensation (diyah) and forgiveness. The two restorative justice models balance protection, access, and obligations in the inforcement of legal and social justice.   Abstrak: Hukum Islam memiliki karakter khusus yang membedakannya dengan sistem hukum yang lain. Dalam restorative justice system, Islam mengintegrasikan aspek legal, moral, dan spiritual dalam penegakkannya. Integrasi ketiga aspek tersebut terlihat dalam filosofi hukum, konstruksi hukum, penetapan tindakan dan sanksi hukum. Artikel ini mengeksplorasi bagaimana integrasi ketiga aspek tersebut membentuk model keadilan restoratif, melalui pengklasifikasian otoritas (ḥuqūq) dalam hukum Islam. Dalam penetapan hukum, klasifikasi hak Tuhan, hak manusia, dan campuran antara hak Tuhan dan hak manusia menentukan perbedaan model penegakkan keadilan restoratif. Aturan hukum yang berada dalam otoritas Tuhan (ḥuqūq Allāh) menghasilkan model penegakan keadilan restoratif yang berpusat pada pelaku tindak pidana, melalui hukuman yang berupa taubat dan kaffārāt. Aturan hukum yang berada dalam otoritas manusia (ḥuqūq al-’abd) dan campuran otoritas Tuhan dengan otoritas manusia menghasilkan model keadilan restoratif yang berpusat pada korban, yaitu melalui penerapan hukum kompensasi (diyat) dan pemaafan terhadap pelaku. Kedua model keadilan restoratif ini bertujuan untuk memberikan keseimbangan perlindungan, akses, dan kewajiban dalam penegakan keadilan hukum dan keadilan sosial.